2007
DOI: 10.5424/srf/2007163-01014
|View full text |Cite
|
Sign up to set email alerts
|

Absence of ecotypic differentiation in Mediterranean stone pine in a Spanish inland region

Abstract: IntroducciónEn la selección de materiales de base para obtener semillas o plantas con unos requisitos mínimos de calidad genética y de adaptación para su uso en la regeneración artificial o repoblación forestal, la actuación del gestor forestal está condicionada por el marco legislativo de la Unión Europea, España y las Comunidades Autónomas así como por el avance del conocimiento científico y técnico en las últimas décadas. En España, el actual marco legal se define en el Real Decreto 289/2003Decreto 289/ (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…In this study, the tree height reached at 19 years after planting showed statistically significant differences among provenances, as previously reported in several studies (Gordo et al 2007, Mutke et al 2010, Carrasquihno & Gonçalves 2013. The best performance of Spanish provenances in terms of DBH and crown diameter could be explained by the more arid conditions in their area of origin compared with those of the other provenances, allowing a better adaptation of the Spanish provenances to the conditions of the trial site in Casablanca.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, the tree height reached at 19 years after planting showed statistically significant differences among provenances, as previously reported in several studies (Gordo et al 2007, Mutke et al 2010, Carrasquihno & Gonçalves 2013. The best performance of Spanish provenances in terms of DBH and crown diameter could be explained by the more arid conditions in their area of origin compared with those of the other provenances, allowing a better adaptation of the Spanish provenances to the conditions of the trial site in Casablanca.…”
Section: Discussionsupporting
confidence: 85%
“…Evaristo et al (2002) using RAPD markers classified 22 provenances from Portugal, Spain, Italy, Greece, Morocco, Turkey and Israel into four close genetic groups, being the Italian and Portuguese provenances those showing the highest and lowest genetic diversity, respectively. Gordo et al (2007) detected almost null differentiation between stands from the Meseta Norte (Spain) provenance. found very low genetic diversity in Pinus pinea using 12 paternally-inherited chloroplast microsatellites (see also Allal et al 2011).…”
Section: Introductionmentioning
confidence: 99%